ENHANCING DATA SECURITY BY BLOCKCHAIN TECHNOLOGY: INVESTIGATING THE EFFECTIVE EXECUTION OF DIGITAL TRANSFORMATION INITIATIVES IN INDONESIA - Suryawijaya, Tito Wira Eka; Wibowo, Mochammad Eric Suryakencana (Global and Policy Journal of International Relations, 2023)
Digital transformation has affected various aspects of our lives, starting from the way we communicate, work, shop, and do business. In Indonesia, the use of blockchain technology for data security has great potential to increase security and transparency in data management. The use of blockchain technology for data security is an interesting and innovative solution. However, amidst the great potential benefits, the use of blockchain technology also carries risks and challenges that cannot be ignored. The research methodology was carried out using a qualitative descriptive approach by analyzing data and information obtained from reliable sources such as journals, books, articles, reports and official documents related to digital transformation and the implementation of blockchain technology in Indonesia. In addition, this research also involves interviews with experts and practitioners in the field of technology and digital transformation in Indonesia. The concept of data security includes three main aspects: confidentiality, integrity and availability of data. Data confidentiality relates to the privacy and confidentiality of data from unauthorized parties. Information categorized as confidential includes personal data, health data, financial data, company confidential data, and government data. The Indonesian government has paid attention to this potential and issued regulations and strategies to increase the use of blockchain technology in government and private sector operations. Several projects using blockchain technology in Indonesia have been carried out, such as verifying and validating educational certificates, storing medical data, and using cryptocurrency as a means of payment.DOI : https://doi.org/10.33005/jgp.v11i02.4138